CAPITAL FORMATION AND UNEMPLOYMENT IN NIGERIA (1985–2024): EVIDENCE FROM ARDL APPROACH - Tubotamuno, Boma; Oladosu, Isaac (African Journal of Social and Behavioural Sciences, 2025)
This study empirically appraised the effect of capital formation on unemployment in Nigeria from 1986 to 2024. The study utilised annual time series data from the National Bureau of Statistics (NBS) and the World Development Indicators (WDI) of the World Bank. The data analysis techniques adopted comprise the Autoregressive Distributed Lag (ARDL) approach, bounds cointegration test, and ADF unit root test. The study found that the unemployment rate in Nigeria is significantly diminished by gross fixed capital formation and net fixed capital formation, while national saving has a negative and non-significant impact on the unemployment rate. The study concluded that capital formation plays a significant role in reducing unemployment in Nigeria. The implication of this is that policies aimed at promoting capital accumulation can serve as effective tools for unemployment reduction. It shows that capital formation is not only enhancing output (GDP) but also translating into inclusive growth by creating jobs. Therefore, the government should prioritise and increase investments in critical infrastructure projects, including energy generation (power plants), industrial zones, and transportation networks (roads, railways, ports). These investments should concentrate on high-impact sectors that generate considerable employment opportunities and stimulate economic activity.